2017
DOI: 10.1101/186775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The widespread misconception about the Japanese major biogeographic boundary, the Watase line (Tokara gap), revealed by bibliographic and beta diversity analyses

Abstract: The biota of the Japanese Archipelago is divided into the Palearctic and Oriental realms by the Watase line (Tokara gap), a major biogeographic boundary of Japan. This boundary is generally placed between Akusekijima and Kodakarajima Islands of the Tokara Archipelago, and has been the subject of many biogeographic debates. However, despite being widely accepted, the position of the boundary is doubtful because of a lack of clear evidence. Here, to verify the definition and existence of the biogeographic bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Nakabayashi et al [31] found three genetically distinct lineages of A. hyacinthus using microsatellite markers and confirmed the presence of only one A. hyacinthus lineage within the temperate region. This divergence between mainland Japan and the Ryukyus has also been observed for a number of terrestrial (reviewed in [32]) and marine species [33]- [42] between the terrestrial biogeographical barrier called the Watase line (also referred to as the Tokara gap). This temperate-subtropical genetic separation has been attributed to allopatric speciation during glacial maximums [39], [41]- [43], the opening and closing of oceanographical barriers facilitated by shifts in the Kuroshio current during glacial maximums [34], [35], [40], [43], and divergent environmental selection pressures [36], [37], [44].…”
Section: Introductionsupporting
confidence: 53%
“…Nakabayashi et al [31] found three genetically distinct lineages of A. hyacinthus using microsatellite markers and confirmed the presence of only one A. hyacinthus lineage within the temperate region. This divergence between mainland Japan and the Ryukyus has also been observed for a number of terrestrial (reviewed in [32]) and marine species [33]- [42] between the terrestrial biogeographical barrier called the Watase line (also referred to as the Tokara gap). This temperate-subtropical genetic separation has been attributed to allopatric speciation during glacial maximums [39], [41]- [43], the opening and closing of oceanographical barriers facilitated by shifts in the Kuroshio current during glacial maximums [34], [35], [40], [43], and divergent environmental selection pressures [36], [37], [44].…”
Section: Introductionsupporting
confidence: 53%
“…Documents including articles and books referred to in any of the above-mentioned documents were further checked. A preprint related to the current study published in bioRχiv was not considered (Komaki & Igawa, 2017).…”
Section: Document Surveymentioning
confidence: 99%
“…The island is characterized by a unique wet climate, which ranges from subtropical to high alpine climates, and hosts numerous endemic species ( Yahara et al 1987 ; Smith and Kamiya 2006 ; Shibasaki 2018 ). Yakushima is located in the southern boundary of Palearctic faunal realm, and the new biogeographic boundary between the Palearctic and Oriental realm was proposed between Yakushima/Taneshima and Amami Islands ( Komaki and Igawa 2017 ). The crane fly fauna of the island is poorly known, at the moment only six species are known as endemic to the island; however, the second author has an additional 8–10 undescribed species from Yakushima.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%